Implementasi Hukum Permintaan Minuman Es Teh Jumbo pada Pasar Malam Bunderan Jombang: Antara Teori dan Praktik - Prastyo, Alfin; Sopingi, Imam; Yuni, Kusnul (Politeknik Baubau, 2025)
Demand for jumbo iced tea drinks at the Bunderan Jombang night market shows unique dynamics that cannot be fully explained by conventional demand laws. In addition to price, factors such as promotions, flavor innovation, social trends, and the influence of digital media play an important role in consumer purchasing decisions. This phenomenon is interesting to study because it reflects how consumer behavior in traditional markets is influenced by economic, social, and psychological aspects simultaneously. This study aims to analyze the application of the law of demand in the context of night markets and uncover the non-price factors that influence the demand for jumbo iced tea. Using a qualitative method with a phenomenological approach, this study collected data through direct observation, in-depth interviews with traders and consumers, and documentation of market activities. Data analysis was conducted by highlighting consumers' experiences and perceptions regarding the factors that drive their purchasing decisions. The results show that quantity-based promotions, such as “buy one get one free,” are more effective in increasing demand compared to direct price reductions. This strategy increased sales by 40%, while price discounts only resulted in a 12% increase in demand. In addition, flavor innovation, strategic location, and virality on social media play an important role in attracting consumers. Seasonal factors also come into play, with a spike in demand in the summer and a decline during the rainy season. This research confirms that the law of demand remains relevant but needs to be understood in a broader context, including social and psychological aspects. The findings provide insights for businesses in designing more innovative marketing strategies as well as for academics in understanding the complexities of consumer behavior in traditional markets.